Analysis of Indoor Environmental Quality Influence toward Occupants’ Work Performance in Kompleks Eureka, USM - Mohamad Rizal Zainon; Faizal Baharum; Loh Yong Seng; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2016)
Indoor environment much more important for people health and comfort than the outdoor environment for most people who spend most of their living times in industrialized countries lives in an artificial indoor environment. Along these lines, this research is to upgrade indoor environmental quality conditions for comfort and work performance of occupants in Kompleks Eureka, USM while conserving energy of the building. Detailed field investigations of the indoor environment in large office buildings in many parts of the world have documented that the indoor environmental quality is typically rather mediocre, with many people dissatisfied and many suffering from sick-building syndrome symptoms. Recent studies have shown an important impact of the indoor thermal environment on occupants work performance. Also studies on occupants medical leave show a very high loss of work time and working performance, which have important economical consequences for companies. The paper will mainly dealing with the indoor environmental qualities, such as thermal comfort level, air quality, lighting, and acoustic quality. The studies before showing that comfortable room temperatures, increased air ventilation above normal recommendation, comfortable acoustic surrounding will increases the work performance of occupants in Kompleks Eureka, USM.